2016
DOI: 10.1002/adfm.201604208
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Induced Bandgap Optimization in Lead‐Based Perovskites with Prolonged Carrier Lifetime and Ambient Retainability

Abstract: Bond length and bond angle exhibited by valence electrons is essential to the core of chemistry. Using lead‐based organic–inorganic perovskite compounds as an exploratory platform, it is demonstrated that the modulation of valence electrons by compression can lead to discovery of new properties of known compounds. Yet, despite its unprecedented progress, further efficiency boost of lead‐based organic–inorganic perovskite solar cells is hampered by their wider bandgap than the optimum value according to the Sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
201
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(218 citation statements)
references
References 53 publications
14
201
3
Order By: Relevance
“…Benefiting from their excellent band alignment, the PSCs show much lower photon energy loss with a relative large ratio of about 0.80 for open‐circuit voltage ( V oc )/band gap ( E g ), in comparison to the typical value of 0.60 for other types of solar cells . The reported V oc of CH 3 NH 3 PbI 3 /spiro‐OMeTAD based PSCs is close to its theoretical value of 1.33 V according to Shockley–Queisser limitation …”
Section: Introductionsupporting
confidence: 68%
“…Benefiting from their excellent band alignment, the PSCs show much lower photon energy loss with a relative large ratio of about 0.80 for open‐circuit voltage ( V oc )/band gap ( E g ), in comparison to the typical value of 0.60 for other types of solar cells . The reported V oc of CH 3 NH 3 PbI 3 /spiro‐OMeTAD based PSCs is close to its theoretical value of 1.33 V according to Shockley–Queisser limitation …”
Section: Introductionsupporting
confidence: 68%
“…[1] 2D organic-inorganic metal halide perovskites possess a layered sandwich structure composed of alternating organic and inorganic components, giving rise to remarkable quantum confinement effects and large exciton binding energy, in which the generated carries are confined within the inorganic layers. [10] The electronic conductivity of halide perovskite can be greatly enhanced with compression. [2] The bulky phenyl ethylammonium (PEA) organic molecule spacer cation is applied to synthesize 2D or quasi-2D Ruddlesden-Popper lead bromide mild pressure.…”
Section: Broadband Emissionmentioning
confidence: 99%
“…For example, we have experimentally investigated the high‐pressure effect on the properties of organic–inorganic lead halide perovskite CH(NH 2 ) 2 PbBr 3 , and found that its structure undergoes two phase transitions below 2.2 GPa, directly leading to the red shift/blue shift of bandgap and the variation of the colors . Strikingly, upon applying pressure of up to 2.1 GPa, the bandgap of CH(NH 2 ) 2 PbI 3 is reported to experience a red shift from 1.489 to 1.337 eV, which exactly reaches to the optimal bandgap required by Shockley–Queisser efficiency limit . Meanwhile, Jia et al found that CH 3 NH 3 SnI 3 can possess structural stability, increased electrical conductivity, and enhanced photo responsiveness via two sequential compression and decompression cycles .…”
Section: Introductionmentioning
confidence: 99%